The Impact of Digital Transformation on the Dynamic Adjustment of Corporate Capital Structure - Han, Jun (Transactions on Economics, Business and Management Research, 2024)
In the era of digital transformation, the dynamic adjustment of corporate capital structure becomes particularly important. Digital transformation changes the operational model of enterprises, profoundly affecting their capital demand structure, profitability, and risk-bearing capacity, thereby having a profound impact on the dynamic adjustment of capital structure. Digital transformation leads enterprises to focus more on the optimization of technology investment and capital expenditure. As investment in digital technologies increases, the capital demand structure of enterprises changes, requiring them to adjust their capital structure according to actual situations to support the progress of digital transformation. However, digital transformation is not always smooth sailing. The rapid changes in market environment, adjustments in industry competition patterns, and diversification of customer demands pose new challenges to the dynamic adjustment of corporate capital structure. Enterprises that fail to transform or adjust improperly often overlook the dynamic adjustment of capital structure, leading to problems such as capital shortages and risk accumulation. Therefore, enterprises should pay close attention to the dynamic adjustment of capital structure during digital transformation, formulate reasonable capital structure strategies according to actual conditions and changes in the external environment, to achieve sustainable development.